Letter to Jane Tolmach from John T. Conlan - John T. Conlan:::::: (1970)
A letter to Jane Tolmach from Supervision John T. Conlan informing her of the time and date of the next Environmental Impact Study ad hoc Citizens Advisory Committee. Mentions that the purpose of the meeting is to discuss the reports and prepare a presentation to the Board of Supervisors.